People management and sustainability: building paths through the capacitation practices - Oliveira, Jefferson Menezes de; Estivalete, Vania de Fátima Barros; Andrade, Tais de; Costa, Vívian Flores (Revista de Administração da UFSM, 2017)
This study seeks to identify how the issue of sustainability is manifested between the capacitation actions offered by the people management area of an institution of higher education. With qualitative approach, the study is developed by performing three steps: (i) analysis of strategic documents of the institution; (ii) mapping of capacitation actions on sustainability offered to servers; and (iii) semi-structured interviews analysis performed with the servers involved in the organization and dissemination of capacitation actions. The results showed that the institution recommends sustainability in their strategic documents, with convergence to the ecological dimension in their actions. The servers involved in the organization and dissemination of capacitation actions understand that the people management area takes on a strategic role in addressing sustainability in an integrated manner with other institutional actions. However, there are difficulties in offering permanent training, since there is a shortage of specialists available to disseminate the theme in its entirety, thus indicating the permanent offer of training involving sustainability.